The influence of music education and sports psychology on students' anxiety - Shihao Zhang , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Music contains some folk culture, national culture, and foreign culture. This type of aesthetic gratification from music can instill in students the desire for self-actualization, which is crucial for enhancing their artistic talent and charisma. This investigation aims to determine the effect of music education and sports psychology on student anxiety. This information was taken from 200 college students randomly picked from a Chinese university. The findings of this study revealed that music education and sports psychology substantially impact student anxiety. The study concluded that a student's anxiety could be lessened by providing a suitable education. The study has theoretical ramifications that have realistically expanded the body of knowledge. In addition, the practical consequences of this study are essential for enhancing the sports psychology of students. There are also some future directions for this research.